Words in the mind : an introduction to the mental lexicon - Aitchison, Jean. (Singapore : Wiley Blackwell, 2012)
Words in the Mind is all about words: how we learn them, remember them, understand them, and find the precise ones we wish to use. It also addresses the structure and content of the human word-store- the "mental lexicon' - with particular reference to the spoken language of native English speakers. Great strides have been made in our understanding of the lexicon since first three editions of Word in the mind were publishes, and it has developed into a major interests of study among linguists, psychologists, sociologists, and those who teach English as a second language.
Part1. Aims and Evidence -- Part2. Basic Ingredients -- Part3. Newcomers -- Part4. The Overall Picture
Includes bibliographical references and index.
Keywords: LANGUAGES